Avaliação do efeito adjuvante da terapia fotodinâmica antimicrobiana no tratamento periodontal de indivíduos com síndrome de Down - Silva, Maria das Graças Barbosa da (2018)
Down syndrome (DS), also known as trisomy 21, is associated with various craniofacial and dental abnormalities. One of the main oral clinical repercussions in DS is the presence of periodontal disease, which has some characteristics, such as: chronic generalized marginal gingivitis, gingival augmentation, alba matter, spots, calculus, gingival recession, tooth mobility and periodontal pocket formation. Photodynamic antimicrobial therapy (aPDT) has been one of the main adjuvant therapies in conventional treatment of periodontal disease because it allows reduction of periodontopathogens, with no systemic side effects. The objective of this study was to evaluate the effectiveness of aPDT, associated to scaling and root planing, in non-surgical periodontal treatment in individuals with DS. The sample included 8 individuals with DS, aged between 17 and 38 years old, of both sexes, presenting chronic periodontitis. Participants were attended at four times: baseline, where were evaluated the Plaque Index (PI), Bleeding on Probing (BOP), probing pocket depth (PPD) and Clinical Attachment Level (CAL); in the initial treatment, scaling and root planing were performed full mouth and two quadrants were randomly selected for application of aPDT; One month after the initial treatment, the reevaluation was done. The data were analyzed using the Wilcoxon test (α = 0.05). No changes were observed in PI (p> 0.05). The BOP values were lower in the reevaluation (p <0.05). PPD and CAL reductions were observed both in the teeth of the test group and in the teeth of the control group, with a statistically significant difference relation to the baseline (p <0.05). The findings of the present study show that both treatments result in clinical improvements in the treatment of periodontal disease in patients with DS.